Evaluation of the Effect of the ENSO Cycle on the Distribution Potential of the Genus Anastrepha of Horticultural Importance in the Neotropics and Panama (2023)
Climate variability has made us change our perspective on the study of insect pests and pest insects, focusing on preserving or maintaining efficient production systems in the world economy. The four species of the genus Anastrepha were selected for this study due to their colonization and expansion characteristics. Models of the potential distribution of these species are scarce in most neotropical countries, and there is a current and pressing demand to carry out this type of analysis in the face of the common scenarios of climate variability. We analyzed 370 presence records with statistical metrics and 16 bioclimatic variables. The MaxEnt method was used to evaluate the effect of the ENSO cycle on the potential distribution of the species Anastrepha grandis (Macquart), Anastrepha serpetina (Wiedemann), Anastrepha obliqua (Macquart), and Anastrepha striata (Schiner) as imported horticultural pests in the neotropics and Panama. A total of 3472 candidate models were obtained for each species, and the environmental variables with the greatest contribution to the final models were LST range and LST min for A. grandis, PRECIP range and PRECIP min for A. serpentina, LST range and LST min for A. obliqua, and LST min and LST max for A. striata. The percentage expansion of the range of A. grandis in all environmental scenarios was 26.46 and the contraction of the range was 30.80; the percentage expansion of the range of A. serpentina in all environmental scenarios was 3.15 and the contraction of the range was 28.49; the percentage expansion of the range of A. obliqua in all environmental scenarios was 5.71 and the contraction of the range was 3.40; and the percentage expansion of the range of A. striata in all environmental scenarios was 41.08 and the contraction of the range was 7.30, and we selected the best model, resulting in a wide distribution (suitable areas) of these species in the neotropics that was influenced by the variability of climatic events (El Niño, Neutral, and La Niña). Information is provided on the phytosanitary surveillance systems of the countries in areas where these species could be established, which is useful for defining policies and making decisions on integrated management plans according to sustainable agriculture. Keywords: geographic distribution; ENSO Anastrepha; horticulture; neotropics; Panama